Badlands Bloodsport - Sharpe, Jon (Sharpe, Jon, Renegade rifles., 2012)
The Trailsman must either kill or be killed when he, along with a group of stuffy tinhorns under his protection, comes upon a Cheyenne buffalo hunt.